Continuity of the free boundary in elliptic problems with Neuman boundary condition - Abderachid Saadi (Electronic Journal of Differential Equations, 2015)
We show the continuity of the free boundary in a class of two dimensional free boundary problems with Neuman boundary condition, which includes the aluminium electrolysis problem and the heterogeneous dam problem with leaky boundary condition.